Research on the distribution law of downward mining stress field in close-distance coal seam and reasonable location of the roadway - Hongtao LIU; Zhou HAN; Zijun HAN; Xiaofei GUO; ShengJie WEI; Zilong LUO; Zhengbao HU (Meitan kexue jishu, 2024)
The formation of residual coal pillars and void areas after mining of the upper seam close to the coal seam will affect the layout of the lower seam roadway. In this paper, taking 231101 working face of Xinliu Mine as engineering background, the comprehensive research means of theoretical analysis and numerical simulation is used to study and analyze the stress evolution law of mining stress field after overlying coal seam mining, and conduct an in-depth investigation on the asymmetric deformation damage mechanism of lower coal roadway, so as to arrive at the reasonable location of lower coal roadway layout. The research results show that: ① the overlying coal seam mining changes the principal stress magnitude, principal stress ratio and stress deflection angle at the location of the roadway, and the change of stress vector is the main reason for the asymmetric damage of the roadway. ② At 11 m from the center of the coal pillar, the maximum principal stress of the surrounding rock of the roadway reaches 14.43 MPa, the principal stress ratio is 2.74, and the stress deflection angle is 52.33°. At this time, the roadway is in a poor stress environment, resulting in butterfly-shaped damage of the surrounding rock and the rotation of the butterfly leaf to the right side of the roof of the roadway, and the right side of the roof of the roadway is prone to roofing accidents. ③ In order to make the roadway in a relatively stable area, this paper divides the working area into four zones based on three main influencing factors, and suggests that the best layout area is H–IV after considering the economic and safety factors of the coal mine, with the main stress deflection angle in the range of 0°−38° or 45°−90°.